Sex differences on cognitive reflection - Olalde, Blanca Rosa; Palacios, Santiago (Anales de Psicología / Annals of Psychology, 2023)
The Cognitive Reflection Test or CRT is a popular measure designed to distinguish the intuitive thinking processing from the analytical one. Sex differences in the CRT have been found in multiple studies. In this research, the influence of the mathematical component on sex differences is studied by using two different instruments to measure cognitive reflection: the original CRT and one extended version of the original one, both with a high arithmetic component and, on the other hand, a set of five classic heuristic tasks, called CHT, with a lower numeracy content. The results show that these sex differences disappear when the mathematical nature of the tasks is reduced. Finally, in this work a more elaborate way of scoring the intuitive responses is addressed in relation to the meaning of these differences.